Theoretical IR spectroscopic study of Copper Phthalocyanine (CuPc) - Hussein, M. T. (Nahrain University College of Engineering Journal, 2008)
The mobile electron of Phthalocyanine can serve as current carries and provide the basis for semiconductor properties and to increase thecurrent carries by substituting with Copper metal. The modes of vibration recorded for CuPc were (165) with vibrational frequencies recorded in theregion (15- 3080)cm-1,intensity and symmetry for each mode were interpreted on the basis of using HyperChem 6.0 semi-empirical molecular orbitalof self consistent field of MNDO method (Modified Neglected of Differential Overlap) of parameterization PM3 involving a quantum mechanical semi-empirical Hamiltonian with restricted and unrestricted Hartree-Fock approximation. The high occupied molecular orbital (HOMO) and low unoccupied molecularorbital (LUMO) were (-4.986 and -2.222)eV respectively. The energy gap calculation ( E) was (2.764) eV, the ionization potential (I.P.) was(4.986) eV and electron affinity (E.A.) was (2.222)eV . Other characteristic such as dipole moment, the charge density and electrostatic potential were plotted with a contour diagram, using both two and three dimensions. The results suggest that CuPc has anomalous behavior than metal-free phthalocyanine H2Pc. Such behavior was ascribed to the bonding nature of the central Cu ion differing from that of other metal derivatives. We can suggest that CuPc hasattracted much attention as a potential candidate for device applications.